2015
DOI: 10.1108/el-06-2014-0094
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of the mobile library service system success model

Abstract: Purpose – The purpose of this study is to develop and analyse the usage status, level of satisfaction and success model of a mobile library service system in Taiwan. The research results could serve as a reference for the development, evaluation and improvement of libraries’ mobile services. Design/methodology/approach – This study designed a mobile library service system and used the informational system success model to evaluate its us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 36 publications
4
39
1
Order By: Relevance
“…A study by Yueh Min Huang et al (2015) shows that e-resources and digital libraries are becoming increasingly important channels for obtaining information. A large number of libraries have consequently introduced mobile communication technologies into their library services, enabling users to search for information from anywhere and at any time.…”
Section: Results and Findingsmentioning
confidence: 99%
“…A study by Yueh Min Huang et al (2015) shows that e-resources and digital libraries are becoming increasingly important channels for obtaining information. A large number of libraries have consequently introduced mobile communication technologies into their library services, enabling users to search for information from anywhere and at any time.…”
Section: Results and Findingsmentioning
confidence: 99%
“…Blake et al (2016) provided evidence of face validity, item validity, and construct validity within their study; Huang et al (2015) demonstrated testing for face validity and construct validity; and Masrek and Gaskin (2016) also showed evidence of a combination of face validity and construct validity. Blake et al changed their survey "to reflect the responses received from librarian reviews and campus interview sessions," and consulted instrument development experts who helped them address content (item) and internal structure (construct) validity components (p. 227).…”
Section: Multiple Examples Of Validity Evidencementioning
confidence: 97%
“…Respondents were asked to consider aspects of librarian behaviour such as approachability and responsiveness, helpfulness, respect for confidentiality, and offering referrals; and aspects of librarian performance such as ability, accuracy, knowledge, and inspiring confidence. Five instruments (Blake et al, 2016;Butler & Byrd, 2016;Huang, Pu, Chen, & Chiu, 2015;Jacoby et al, 2016;Luo & Buer, 2015) asked students to gauge their likeliness to use, re-use, or recommend the service. Masrek and Gaskin reported presenting respondents with 10 items about Service quality, usefulness, and satisfaction (p. 42) but unfortunately did not provide the full text of the items within their article, making it impossible to determine how they conceptualized these elements of satisfaction.…”
Section: Q1: How Did Lis Researchers Gather Data On Patron Satisfactimentioning
confidence: 99%
See 2 more Smart Citations